FAKTOR-FAKTOR YANG MEMPENGARUHI KELEMAHAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH - El Husna M, Siti Latifah; Taufik, Taufeni; Wahyuni, Nita (Jurnal Kajian Akuntansi dan Auditing, 2024)
This research aims to examine the influence of regional complexity, regional government size, economic growth, capital expenditure, local original income, on the weaknesses of the government's internal control system in districts/cities in Riau province in 2013-2022. The population in this study consists of Regencies/Cities in the Riau province from 2013 to 2022, totaling 12 regencies/cities with a 10-year observation period, resulting in a population count of 120. The sampling technique used in this research is purposive sampling, with a total of 33 samples obtained. The sampling was determined in advance based on criteria, the samples taken were districts/cities in Riau Province that did not obtain an Unqualified Opinion (WTP) from the Financial Audit Agency (BPK) in 2013-2022. The data analysis method used in this research employs multiple regression analysis, utilizing the SPSS data processing software version 26. The results of this study indicate that regional complexity, the size of local government, economic growth, and local revenue have an influence on the weaknesses of the internal control system of the government. Capital expenditure does not affect the weaknesses of the internal control system of the government.